(untitled) (Palimpsesto, 2022)
Chicas muertas, by Selva Almada (2014), is part of a process of (re)writings that begins with “La chica muerta” (2007) and branches out in different later texts by the author. Our paper addresses this process. We start with an analysis of “La chica muerta”, which underlines the features that make it a relatively autonomous text, capable of detaching itself from its original context. Next, we consider Chicas muertas (2014) and “La muerta en su cama” (2015) as rewritings of the first story. Although both arise from an authorial attempt to elude the inaccuracies in the narrative reconstruction of Andrea Danne’s crime, strictly speaking the basic core of the facts will remain unknown. It will be the construction of a series of crimes and their reinterpretation as femicide that will provide a possible key of meanings to narrate the events.